COMMUNITY RESILIENCE TO FLOOD AND POLDER DEVELOPMENT PLAN IN CITARUM WATERSHEED (Case Study in Cieunteung, Baleendah Village, Baleendah Sub-District, Bandung District) - Ghani Ilmannafian, Adzani
ABSTRACT COMMUNITY RESILIENCE TO FLOOD AND POLDER DEVELOPMENT PLAN IN CITARUM WATERSHEED (Case Study in Cieunteung, Baleendah Village, Baleendah Sub-District, Bandung District) By Adzani Ghani Ilmannafian 21314006 (Program Study of Magister Biomanajemen) Cieunteung, one of area in Baleendah, which is passed by the tributary of Citarum (Cisangkuy and Cigado), has been affected by flood regularly in rainy season because the contours of the land is lower than Citarum water level. In order to minimize the impact of flood, the government has polder development plan, as a way to control flood completed by drainage systems, retention ponds, dikes, pumps and floodgates, as an integrated water management system that inseparable. Regardless of the potential benefits of polder system, development requires adaptability in Cieunteung to manage the changes. This study aimed to assess the adaptive capacity of the Social-Ecological Systems (SES) Cieunteung to flood and polder development plan, through the resilience approach. Resilience is defined as the ability of a system/society to adapt in crisis and changes of environment without changing the configuration of system fundamentally. This research method is case study. Respondents in this study were Cieunteung society who have not moved as many as 30 individuals, determined by simple random sampling technique, and who have moved and lived in Baleendah’s flat as many as 29 individuals, determined by census techniques. Primary and secondary data were analyzed descriptively by using historical analysis (Citarum temporal study) and content analysis (in-depth discussion of the contents information based framework on existing theory) to analyze Cieunteung community resilience to flood and polder development plan. Based on adaptive cycle, it was known social-ecological system of Citarum is in release phase (?) and still has not reach reorganization phase (?). It also occurs in social-ecological system of Cieunteung community due to flood occurs continously, despite the construction of polder can help the community are in reorganization phase. This is supported by good public perception and the adaptation of polder development. Community have good value on three indicators of resilience (knowledge, skill and learning, social networks, positive outlook), and is expected to increase resilience through the improve of six other indicators leadership, engaged governance , values and beliefs, people-place relationship, common infrastructure, and diverse and innovative economy